A Mechanistic 1D Finite Element Model for Nonlinear Analysis of FRP-Strengthened Reinforced Concrete Beams. Issue 12 (December 2013) - Valipour, Hamid R.; Foster, Stephen
An efficient frame finite element (FE) is developed and applied for nonlinear analysis of reinforced concrete beams flexurally strengthened with externally bonded fibre reinforced polymer (FRP) strips/plates. The developed nonlinear model is able to capture different failure modes associated with concrete crushing and cracking, yielding of steel, FRP rupture and intermediate crack-induced debonding of FRP sheets/plates. The element is formulated using force interpolation concept and a simple approach based on application of discrete springs and linear interpolation of bond forces along the element axis is adopted to take account of shear-slip. The developed formulation and analytical tool are employed to predict the loading capacity and the load-deflection response of reinforced concrete beams strengthened with FRP and the numerically simulated responses agree well with the corresponding experimental results. The major features of this frame element are its simplicity and efficiency compared with more complex FEs which makes it a suitable tool for practical use in design-oriented parametric studies.